Bibliometric analysis of research in ethical concerns and dilemmas of digital mental health care in the last two decades - Sharma, Poonam; Wagani, Rekha; Varghese, Mahima Anna (Frontiers in Human Dynamics, 2025)
IntroductionDigital mental health care system includes the interventions delivered via digital technologies, such as mobile apps, websites, or virtual reality (VR). A recent upsurge in the digital mental healthcare care services has been observed in the last 5 years. With its core advantage of reaching the unreached, wider coverage, cost and time effectivity, all eyes are on the digital mental health care system. It is definitely a mechanism to cater rising prevalence of mental health concern, stigma towards mental health, accessibility and cost and uplift the psychological wellbeing. Success of the digital mental health care system has been researched world-wide. However, the same is not unaffected by the ethical concerns.MethodsThis study aims to perform a comprehensive bibliometric analysis of scholarly articles on ethical concerns and dilemmas of digital mental health care by utilizing data extracted from the Scopus database from 2000 to 2024 by analysing 123 research articles. Statistical descriptive analysis in combination with performance analysis and co-word analysis was used to understand the research trends, leading countries and country collaborations studying ethical concerns related to digital mental healthcare.Result and discussionThe first publication appeared in 2000 with zero research till the year 2005. In this decade till 2010 we can observe only 4 publications. Consistent publishing started trending upward through 2018, observing the largest increase during pandemic in 2020 and onwards constituting 100 publications. The United States of America is the leading country studying ethical dilemmas in Digital Mental healthcare, with 42 papers followed by United Kingdom with 23 publications. The most influential peace of research with 490 citations is article co-authored by Barak et al. (2009), which is defining internet-supported therapeutic interventions and related concerns. BMJ Open is noted as the leading journal which is publishing issues concerning Digital Mental Healthcare with 18 publications, followed by Frontiers in Psychiatry and JMIR Mental Health. Analyses reflects that the top cited articles on Digital Mental healthcare are specifically directed on bringing out some of the key concerns of data privacy, emergency response, therapist competency and consent which requires appropriate handling Otherwise they may be cause of distress to client and question the trustworthiness of the Digital Mental Health Care system.ConclusionThe concerns brought out through this bibliometric analysis could be important guiding principles for online mental health services. Alongside, mental health professionals operating online must have orientation on the ethical concerns surrounding online mental healthcare.